Pharmaco-economical analysis of Russian QUADRIGA Study data - A. A. Kuprina; Yu. B. Belousov (Кардиоваскулярная терапия и профилактика)
Aim. To assess antihypretensive effect quality and duration for ACE inhibitor spirapril (Quadropril®; daily dose 6 mg) among arterial hypertension (AH) patients, in real-world out-patient clinical settings. Material and methods. The trial involved 11 Russian cities. This Russian multi-center, non-comparative, open study QUADRIGA (QUADRoprIl and AH) involved 235 AH patients with Stage I-II of blood pressure (BP) elevation; systolic BP (SBP) 140-179 mm Hg and/or diastolic BP (DBP) 90-109 mm Hg; age 25-75 years (mean age 51.1 years); <60 years – 74.8%, and 60 years – 25.2%; females – 54.5%; 17 patients with coronary heart disease, 32 patients with diabetes mellitus. Effectiveness criteria for Quadrorpil® antihypertensive action: normalization of SBP and/or DBP (<140/90 mm Hg); beneficial antihypertensive effect: DBP decrease 10 mm Hg; SBP decrease 20 mm Hg, in regard to baseline BP level. Results. During Quadropril® treatment, as monotherapy or in combination with a diuretic - hydrochlorthiazide was additionally administered to 122 patients (51.9%) - daily dose increase up to 25 mg was necessary in 78 participants; significant SBP and DBP reduction was observed. On average, SBP decreased from 159.8 to 132.8 mm Hg – by 25.7 mm Hg (16.1%), and DBP decreased from 98.7 to 83.3 mm Hg – by 15.1 mm Hg (15.3%). Target BP was achieved in 83.56% of the patients. Conclusion. According to Russian QADRIGA Study results, a new ACE inhibitor Quadropril® demonstrated good antihypertensive effect. Quadropril® in daily dose 6 mg, once per day, combined with hydrochlorthiazide 12.5-25 mg if needed, can be recommended for AH patients’ treatment.